The "Black Box" Behind Prison-Based Vocational Training Programs - Efrat Shoham; Anat Zelig; Badi Hesisi; David Weisburd; Noam Haviv (European Scientific Journal, ESJ, 2017)
Despite the great importance of prison vocational programs, studies have pointed to a wide variety of barriers that inhibit the released prisoner's chances to integrate into the labor market. The present qualitative investigation was designed to crack the "black box" behind six vocational programs implemented in the Israel Prison Service (IPS). Our findings based on the interviews with all the supervisors in the programs emphasized several factors that seem necessary for the success of the different vocational programs. The interviews show that training in a correctional environment poses a number of major difficulties for the respondents. Furthermore, a significant part of the prisoners' motivation to participate in the training programs is not necessarily related to the desire to find work after release. It was also found that a relatively long training, which makes it possible to find work in the field even during the period of incarceration, holistically addresses the various needs of the prisoner, and corresponds to the job market requirements, increases the chances of its participants to find employment also after their release from prison. When the characteristics of the various programs were examined, it was found that in addition to the characteristics of prisoners, one must also consider structural characteristics such: to what extent do the programs comply with the requirements of the Israeli labor market, confer a formal diploma at the end of the training period, or allow integration into the work force after release.